Martensite heat-resistant steel cast ingot and smelting method and application thereof
Through multi-pass vacuum refining degassing and deep deoxidation technology, the problem of high N content in martensite heat-resistant steel ingots is solved, and the stability control of N content and the improvement of material performance is achieved.
Patent Information
- Application Number
- CN202411509638.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-28
AI Technical Summary
It is difficult to remove nitrogen in existing martensite heat-resistant steel ingots, resulting in high N content, affecting the plasticity and long-lasting strength of the material.
The multi-pass vacuum refining and degassing method is used, combined with vacuum carbon deoxygenation and deep deoxygenation technology of elements such as Zr, Ce, and La, to control the N content of the molten steel to be within 0.006-0.012%.
The stable control of the N content of martensite heat-resistant steel is achieved, and the processing plasticity and long-lasting service performance of the material are improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of smelting, and in particular to a martensitic heat-resistant steel ingot and a smelting method and application thereof. Background Art
[0002] Martensitic heat-resistant steel usually contains 8-17% Cr, which plays an anti-oxidation and strengthening role. However, a high Cr content will reduce the degassing reaction rate during vacuum refining. When using electric furnace + LF + VD or similar methods to produce martensitic heat-resistant steel, the finished product O content is usually higher than 0.002% and the N content is higher than 0.015%. At the same time, in order to improve the long-lasting creep strength, grain boundary strengthening elements such as Zr and B are added to martensitic heat-resistant steel. When the N content is high, large-sized liquid precipitation primary nitrides are easily formed at the end of solidification, which damages the plasticity and long-lasting strength of the material.
[0003] In order to reduce the gas content in martensitic heat-resistant steel, many methods have been proposed, including extending the vacuum refining time, increasing the number of vacuum refining times, etc. However, vacuum refining accompanied by argon stirring will cause the temperature of the molten steel to continue to decrease, and it is necessary to increase the temperature of the molten steel in the previous LF refining stage, or to increase the temperature through LF refining multiple times, which has an adverse effect on the quality of the molten steel, the refractory materials of the ladle, etc., resulting in a decrease in the purity of the molten steel.
[0004] In addition, from the perspective of metallurgical reaction mechanism, reducing the O and S content in molten steel helps to improve the surface activity of molten steel and promote the denitrification reaction. However, in order to avoid the precipitation of harmful phases during long-term service at high temperature, martensitic heat-resistant steel has strict restrictions on the content of deoxidizing elements such as Si and Al, requiring the Al content to be less than 0.015% and the Si content to be less than 0.2%. It is impossible to effectively reduce the O content by precipitation deoxidation. The O content in molten steel can also be increased by adding iron oxide scale, and the vacuum carbon deoxidation reaction is used to generate CO bubbles to increase the surface area of the denitrification reaction to promote denitrification. However, the iron oxide scale contains a large amount of impurity elements, and this method can improve the degassing efficiency in the early stage of the reaction. When the O content drops to the same level before the addition of the iron oxide scale, the degassing reaction efficiency does not change much.
[0005] Therefore, in order to achieve ultra-low N control in martensitic heat-resistant steel, it is necessary to consider multiple aspects such as process, equipment and metallurgical reaction mechanism. Summary of the invention
[0006] In view of the above analysis, the present invention aims to provide a martensitic heat-resistant steel ingot and a smelting method and application thereof, so as to solve the problem that denitrification in existing martensitic heat-resistant ingots is difficult.
[0007] In one aspect, the present invention provides a method for smelting a martensitic heat-resistant steel ingot, comprising the following steps:
[0008] S1: Add raw materials into an electric furnace for smelting, and tap steel after the temperature rises to 1620-1650°C, and add C to 0.06% for diffusion deoxidation;
[0009] S2: LF refining stage, active lime and alumina are used to make reducing slag, ferrosilicon alloy is added to make white slag, the temperature is controlled at 1580-1620℃, and it is transferred to the VD station to wait for vacuum degassing;
[0010] S3: VD first degassing, the first degassing treatment is carried out under high vacuum <133Pa, vacuum carbon deoxidation reaction is used to accelerate denitrification, sampling is carried out after the refining is completed, and the slag is removed to re-make high basicity protection slag;
[0011] S4: the molten steel after the first degassing by VD is transferred to the LF furnace for re-refining, and the temperature is raised to 1580-1600°C. According to the sampling results, C is added to the lower limit of the composition range of 0.08%, and the composition of other alloy elements except N is adjusted to the target value, and then at least one of Zr, Ce and La is added in the form of ferroalloy for deep deoxidation. After blowing argon for ≥10 minutes, it is transferred to the VD station for secondary degassing;
[0012] S5: VD second degassing. After VD refining, the N content of the molten steel is tested, C is added to the target composition, and pouring is carried out in a vacuum environment. After cooling and solidification, a martensitic heat-resistant steel ingot is obtained.
[0013] Furthermore, in step S2, the basicity of the reduced slag is not less than 5, and the (FeO) content in the slag is not higher than 0.6%.
[0014] Furthermore, in step S3, the components of the high basicity protective slag are CaO, Al2O3, SiO2 and MgO, and the protective slag basicity CaO / SiO2 is not less than 8.
[0015] Further, in step S4, the addition amounts of Zr, Ce and La satisfy -8 <lg[%Si]+4lg[%Zr]+3.8lg[%Ce]+3.7lg[%La]<-7。
[0016] Furthermore, in step S5, if the composition does not meet the target requirement, Zr, Ce, and La deoxidizers are added again, and then degassing is performed 1 to 2 more times.
[0017] Furthermore, in step S2, the Si content in the molten steel is not less than 0.08%.
[0018] Furthermore, deep deoxidation is performed by using at least one element among Zr, Ce and La, and the residual content of a single element in the molten steel after VD refining does not exceed 0.003%.
[0019] On the other hand, the present invention provides a martensitic heat-resistant steel ingot, whose chemical composition, measured by mass percentage, is: C: 0.08-0.14%; Si: ≤0.2%; Al: ≤0.015%; Mn: 0.35-0.80%; Cr: 8.6-9.5%; W: 1.80-2.55%; Mo: 0.20-0.60%; Co: 2.5-3.2%; V: 0.17-0.27%; Nb: 0.04-0.07%; B: 0.010-0.017%; N: 0.006-0.012%; O: ≤0.002%, and the rest is Fe.
[0020] Furthermore, the smelting method or the application of the martensitic heat-resistant steel ingot is that the martensitic heat-resistant steel ingot is used as a consumable electrode for electroslag remelting, or is directly forged.
[0021] Furthermore, the martensitic heat-resistant steel ingot is used as a consumable electrode for electroslag remelting. The crystallizer is baked before the remelting begins for a time of not less than 20 minutes. After Ar is filled until the O2 content in the furnace is less than 0.2%, power is supplied and remelting is carried out under a protective atmosphere. The slag system uses CaF2-Al2O3-CaO-B2O3-MgO pre-melted slag.
[0022] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0023] 1. The present invention adopts multi-pass vacuum refining and degassing, respectively giving full play to the advantages of vacuum carbon deoxidation to increase the denitrification reaction interface area and high purity refining to improve the denitrification reaction rate, so as to achieve the goal of stably controlling the N content of martensitic heat-resistant steel below 0.012% in the limited refining process.
[0024] 2. The present invention uses Zr, Ce, La and other elements for deoxidation during the refining process to achieve ultra-low O control. At the same time, the added deoxidizing elements are automatically removed by inclusion floating or slag reaction. The residual amount of a single element does not exceed 0.0030%, which is beneficial to the performance of martensitic heat-resistant steel.
[0025] 3. The martensitic heat-resistant steel ingot provided by the present invention contains elements such as B and Cr, and controls the contents of Si, Al and O elements, especially controls the N content in the ingot to be 0.006-0.012%, which helps to exert the grain boundary strengthening effect of the alloy elements, improve processing plasticity, and enhance the long-term service performance of the material.
[0026] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents of the description. DETAILED DESCRIPTION
[0027] Martensitic heat-resistant steel usually contains 8-17% Cr, which plays an anti-oxidation and strengthening role, but a high Cr content will reduce the degassing reaction rate during vacuum refining. When martensitic heat-resistant steel is produced by electric furnace + LF + VD or similar methods, the finished product O content is usually higher than 0.002% and N content is higher than 0.015%.
[0028] At the same time, in order to improve the long-term creep strength, grain boundary strengthening elements such as Zr and B are added to martensitic heat-resistant steel. When the N content is high, large-sized liquid primary nitrides are easily formed at the end of solidification, which damages the plasticity and long-term strength of the material.
[0029] In order to reduce the gas content in martensitic heat-resistant steel, the main methods currently used include: extending the vacuum refining time, increasing the number of vacuum refining times, etc., but most of them will lead to reduced purity of molten steel and the formation of defects such as inclusions in the ingot.
[0030] For martensitic heat-resistant steel with a high Cr content, it is quite difficult to remove N, and it contains B element. Controlling the N content in the ingot at 0.006-0.012% helps to exert the grain boundary strengthening effect of the alloy element, improve processing plasticity, and enhance the long-term service performance of the material.
[0031] The present invention provides a method for smelting a martensitic heat-resistant steel ingot, comprising the following steps:
[0032] S1: Add raw materials into an electric furnace for smelting, and tap steel after the temperature rises to 1620-1650°C, and add C to 0.06% for diffusion deoxidation;
[0033] S2: LF refining stage, active lime and alumina are used to make reducing slag, ferrosilicon alloy is added to make white slag, the temperature is controlled at 1580-1620℃, and it is transferred to the VD station to wait for vacuum degassing;
[0034] S3: VD first degassing, the first degassing treatment is carried out under high vacuum <133Pa, the vacuum decarburization reaction is used to generate CO bubbles, which increases the denitrification reaction interface area and accelerates the denitrification. After the refining is completed, sampling is carried out, and the slag is removed to re-make high basicity protective slag;
[0035] S4: the molten steel after the first degassing by VD is transferred to the LF furnace for re-refining, the temperature is raised to 1580-1600°C, C is added to the lower limit of the composition range of 0.08% according to the sampling results, the composition of other alloy elements is adjusted to the target value, and then at least one of Zr, Ce and La is added in the form of ferroalloy for deep deoxidation, and argon is blown for 10 minutes before being transferred to the VD station for secondary degassing;
[0036] S5: VD second degassing. After VD refining, the N content of the molten steel is tested, C is added to the target composition, and pouring is carried out in a vacuum environment. After cooling and solidification, a martensitic heat-resistant steel ingot is obtained.
[0037] Compared with the prior art, the present invention provides a smelting method, including three stages of smelting, refining and vacuum pouring; in the refining process, LF and VD are combined for refining. No additional precipitation deoxidation is performed in the first LF refining, and the Si and Al contents of the molten steel are controlled to be as low as possible, and the "easy to remove" part of N in the molten steel is removed as soon as possible by vacuum carbon deoxidation reaction; the second LF refining uses at least one of Zr, Ce and La for precipitation deoxidation, and based on the thermodynamic reaction and the calculation results of slag equilibrium, the O content of the molten steel is reduced to below the conventional refining level, thereby improving the subsequent vacuum refining degassing efficiency; if the N content does not meet the standard after the second VD degassing, Zr, Ce and La deoxidizers are added again, and then 1 to 2 VD vacuum refinings are performed until the N content is reduced to below 0.012%.
[0038] Specifically, in step S1, the raw materials include scrap steel, molten iron and ferrochrome, etc., and the N content of the ferrochrome raw material brought into the molten steel should be less than 0.003%.
[0039] It should be noted that the nitrogen content in low-grade ferrochrome raw materials is relatively high. In order to reduce the gas content in the molten steel before vacuum refining, shorten the degassing reaction time as much as possible, and give full play to the advantages of the one-stage degassing reaction, in the present invention, it is necessary to strictly control the N content in the ferrochrome raw materials to ensure that the N content brought into the molten steel by the ferrochrome does not exceed 0.003%.
[0040] Specifically, in step S2, the basicity of the reducing slag is not less than 5, and the (FeO) in the slag is ≤0.6%, so as to avoid oxidation and burning of elements such as Cr and Mn in the molten steel.
[0041] It should be noted that in the present invention, in the LF refining stage, the molten steel or alloy melted in the electric furnace is transferred to the LF furnace, and active lime and alumina are added to the molten steel or alloy to make reducing slag, the purpose of which is to reduce the content of S and O. When making reducing slag, its basicity is required not to be lower than 5. When it is lower than this basicity, the desulfurization and deoxygenation effects of the reducing slag are weakened, thereby affecting the final ingot composition.
[0042] It should be noted that in the first LF refining stage, after adding ferrosilicon alloy, the Si content in the molten steel is not less than 0.08%, ensuring that other elements such as Nb and Cr in the molten steel will not be burned due to excessive O content.
[0043] Specifically, in step S3, the components of the high basicity protective slag are CaO, Al2O3, SiO2 and MgO, and the protective slag basicity CaO / SiO2 is not less than 8.
[0044] Preferably, the high basicity refining slag has the following composition: CaO: 50 - 65%; Al2O3: 30 - 45%; SiO2: 1 - 7%; MgO: 3 - 7%.
[0045] It should be noted that when the basicity is lower than 8, adding deoxidizers Zr, Ce, and La cannot achieve an effective deep deoxidation effect. They mainly enter the slag through the reaction and burning loss of the steel slag, and increase the Si and Al contents in the molten steel.
[0046] Specifically, in step S4, the addition amount satisfies -8 < lg[%Si] + 4lg[%Zr] + 3.8lg[%Ce] + 3.7lg[%La] < -7.
[0047] Specifically, at least one of the elements Zr, Ce, and La is used for deep deoxidation, and the residual content of a single element in the molten steel after VD refining does not exceed 0.003%.
[0048] It should be noted that in the present invention, elements such as Zr, Ce, and La are added as deoxidizers to reduce the oxygen content in the molten steel. When adding deoxidizers, it must satisfy -8 < lg[%Si] + 4lg[%Zr] + 3.8lg[%Ce] + 3.7lg[%La] < -7. When the addition amount is greater than -7, due to 3Zr + 2(Al2O3) = 3(ZrO2) + 4Al, 2Ce + (Al2O3) = (Ce2O3) + 2Al, 2La + (Al2O3) = (La2O3) + 2Al, the Al element content in the molten steel may exceed the standard, and large-sized oxide inclusions will appear in the ingot, which will instead affect its performance; when the addition amount is less than -8, the content of deoxidizing elements in the molten steel is too low to play the role of deep deoxidation and improving the denitrification efficiency.
[0049] In addition, elements such as Zr, Ce, and La are extremely easy to segregate to the grain boundaries, which can reduce grain boundary defects, improve grain boundary bonding force, reduce grain boundary diffusion rate, slow down dislocation climb, and strengthen grain boundaries. Zr-containing carbonitrides can inhibit the growth of austenite grains, refine grain size, and improve the short-term strength and toughness of steel. Ce can accelerate the migration rate of Si to the surface in steel, promote the formation of a dense SiO2 film on the surface, and improve the oxidation resistance. However, the three elements have a very strong affinity for oxygen, and microcracks will be generated when large-sized inclusions are formed, which is不利 to the strength and toughness, damages the fatigue resistance of the material, and causes nozzle caking, affecting the castability.
[0050] Preferably, in the ferroalloy of Zr, Ce and La, the zirconium-iron alloy composition is: zirconium Zr: 25-35%, iron Fe: 65-75%, and the rest are impurities that are difficult to remove, and the iron content in ferrocerium and ferrolanthanum is not less than 40%. After the deoxidation process and the slag reaction, the elements such as Zr, Ce and La are basically completely removed, and the residual content of a single element does not exceed 0.0030%, which has a certain effect on improving the service performance of heat-resistant steel.
[0051] Specifically, in step S5, if the ingredients do not meet the target requirements, step S4 is repeated 1 to 2 times.
[0052] It should be noted that a single VD vacuum refining degassing cannot achieve the goal of N content less than 0.012%. By adding strong deoxidizers such as Zr, Ce, La, etc., the O content of the molten steel is reduced, thereby increasing the surface activity of the molten steel and increasing the rate of N removal in the second VD degassing reaction. After the second VD, it is necessary to detect the N content and adjust the C element to the target composition. When the composition meets the requirements, it is transferred to a vacuum environment (such as a vacuum casting chamber) for casting, and then after cooling, solidification and demolding, a martensitic heat-resistant steel ingot is obtained. However, if the detected composition does not meet the requirements, especially when the N element content exceeds the standard, (according to the S4 ratio) the deoxidizer is re-added, and the degassing is repeated 1 to 2 times until the N element content meets the requirements before casting.
[0053] The invention provides a martensitic heat-resistant steel ingot, which has the following chemical components by mass percentage: C: 0.08-0.14%; Si: ≤0.2%; Al: ≤0.015%; Mn: 0.35-0.80%; Cr: 8.6-9.5%; W: 1.80-2.55%; Mo: 0.20-0.60%; Co: 2.5-3.2%; V: 0.17-0.27%; Nb: 0.04-0.07%; B: 0.010-0.017%; N: 0.006-0.012%; O: ≤0.002%, and the rest is Fe.
[0054] Specifically, the martensitic heat-resistant steel ingot obtained in the present invention is remelted as an electroslag remelting electrode, or is remelted as a vacuum consumable remelting electrode, or is directly forged.
[0055] When using martensitic heat-resistant steel ingots to prepare electroslag ingots, the slag system contains Al2O3, which will react with the B element, 2[B]+(Al2O3)=2[Al]+(B2O3) causing burnout, greatly reducing the B recovery rate and the quality stability of the electroslag ingots, and at the same time causing the Al content in the steel to increase, exceeding the upper limit of the allowable composition. The electroslag ingots require Al: ≤0.015%; B: 0.010~0.017%. In addition, during the electroslag remelting process, N2 in the electroslag remelting environment may enter the protective slag through a dissolution reaction, thereby causing the steel liquid to increase in nitrogen, causing the N content in the final electroslag ingot to exceed the range.
[0056] Therefore, the present invention provides an electroslag remelting method for a martensitic electroslag ingot, comprising the following steps:
[0057] S1: electrode preparation: treating the martensitic heat-resistant steel ingot and performing electroslag remelting as an electrode;
[0058] S2: Pre-melted slag baking: The pre-melted slag of the CaF2-Al2O3-CaO-B2O3-MgO system is baked to remove the internal crystal water, the temperature is not less than 800°C, and the time is not less than 8 hours;
[0059] S3: Remelting: Use high-purity argon as a protective atmosphere for electroslag remelting, control the volume fraction of O2 in the atmosphere to be no higher than 0.02%, insert a consumable electrode rod into the crystallizer, add the pre-melted slag and start to energize at the same time;
[0060] S4: Shrinkage feeding: Before the end of remelting, the melting rate is reduced to feed shrinkage, and the mold is removed after the molten steel is completely solidified to obtain a martensitic heat-resistant steel electroslag ingot.
[0061] Compared with the prior art, the electroslag remelting process designed in the present invention can further reduce the risk of nitrogen increase in the remelting process. Adding a small amount of B2O3 and MgO to the slag can further improve the purity of the molten steel and increase the electroslag remelting yield of the B element, thereby ensuring the optimal ratio of B, N and Al elements and improving the service performance of martensitic heat-resistant steel.
[0062] Specifically, the crystallizer is fully baked before the remelting stage begins, Ar is filled until the O2 content in the furnace is less than 0.2%, and then power is supplied, and smelting is carried out under protective atmosphere conditions.
[0063] Specifically, the heavy melting slag is a pre-melted slag of the CaF2-Al2O3-CaO-B2O3-MgO system, in which the CaF2 content is 45-58%, the Al2O3 content is 15-22%, the CaO content is 18-25%, the MgO content is 1.5-3%, and the B2O3 content is 0.5-2.5%.
[0064] It should be noted that N2 in the electroslag remelting environment may enter the protective slag through a dissolution reaction and cause nitrogen addition to the molten steel. Therefore, the crystallizer needs to be baked before remelting begins, and Ar is filled until the O2 content in the furnace is <0.2% before remelting begins. 1.5-3% MgO needs to be added to the electroslag remelting slag system to reduce the risk of N2 dissolution by forming a protective layer on the surface of the liquid slag, and 0.5-2.5% B2O3 is added to increase the recovery rate of B in the electroslag ingot, while reducing the activity of dissolved N in the slag, further avoiding nitrogen addition, and ensuring that the Al content does not exceed the required range (≤0.015%).
[0065] The present invention proposes to add MgO to the CaF2-CaO-Al2O3 basic slag system to reduce the melting point of the slag system and form a protective film to inhibit air from entering the molten steel; adding a small amount of B2O3 is used to accurately control the composition of the electroslag ingot, improve the purity and composition uniformity of the electroslag ingot, and help reduce the melting temperature of the slag and improve the surface quality.
[0066] Specifically, in step S4, the filling ratio is 0.6-0.9, and the melting rate v=(0.6-0.8)×D.
[0067] It should be noted that the filling ratio refers to the ratio of the consumable electrode to the diameter of the crystallizer; a filling ratio that is too high will lead to a decrease in the slag refining effect and reduce the cleanliness of the steel, while a filling ratio that is too low will increase the depth of the molten pool, reduce the efficiency of inclusion removal and reduce production efficiency. This melting rate is the melting rate of the optimized martensitic heat-resistant steel electroslag ingot. The electroslag ingot prepared at this melting rate has good surface quality and a low risk of internal quality defects.
[0068] In order to more clearly describe the present invention, it is further illustrated by the following examples and comparative examples.
[0069] Example 1
[0070] A method for smelting a martensitic heat-resistant steel ingot comprises the following steps:
[0071] S1: Scrap steel and low-carbon ferrochrome are used as the main raw materials for smelting in an electric furnace. The steel is tapped after the temperature reaches 1630°C, and C is added to 0.06% for diffusion deoxidation.
[0072] The nitrogen content in the low carbon ferrochrome is 0.023%, and the nitrogen element is 0.0017% as calculated by the added amount from the ferrochrome raw material;
[0073] S2: LF refining stage, active lime and alumina are used to make reducing slag, ferrosilicon alloy is added to make white slag, the temperature is controlled at 1580-1620℃, and it is transferred to the VD station to wait for vacuum degassing;
[0074] The basicity of the reduced slag is 4.0; the Si content of the molten steel is 0.07% and the Al content is 0.0006%;
[0075] S3: The first degassing of VD is carried out under a high vacuum of <133 Pa. The first degassing treatment is carried out. The vacuum decarburization reaction is used to generate CO bubbles to accelerate denitrification, and argon is continuously charged for stirring. Sampling is carried out after the refining is completed, and the slag is removed and a high-alkalinity protective slag is remade;
[0076] The composition of the high-alkalinity refining slag is: CaO: 54.52%; Al2O3: 35.6%; SiO2: 4.7%; MgO: 5.18%, and the basicity of the protective slag CaO / SiO2 is 11.6; after the first VD refining is completed, the N content of the molten steel is 0.0127%;
[0077] S4: Transfer the molten steel after the first degassing of VD to the LF furnace for secondary refining. The temperature is raised to 1590 °C. According to the sampling results, C is added to 0.08%, and the components of other alloying elements are adjusted to the right place. Then, 0.02% of metallic Zr is added to the molten steel in the form of ferrozirconium alloy (zirconium Zr: 30%, iron Fe: 70%) for deep deoxidation -8 < lg[%Si] + 4lg[%Zr] = -7.95 < -7. After argon blowing and calming for 10 min, it is transferred to the VD station for secondary degassing; the N content of the molten steel is reduced to 0.0097%;
[0078] S5: The second degassing of VD. After the VD refining is completed, the N content of the molten steel is detected, C is supplemented to the target composition, and pouring is carried out in a vacuum environment. After cooling and solidification, a martensitic heat-resistant steel ingot is obtained.
[0079] The chemical composition of the martensitic heat-resistant steel ingot is: C: 0.011%; Si: 0.12%; Al: 0.010%; Mn: 0.45%; Cr: 9.0%; W: 2.2%; Mo: 0.40%; Co: 2.7%; V: 0.20%; Nb: 0.06%; B: 0.014%; N: 0.0092%; O: 0.0014%, and the rest is Fe.
[0080] Example 2
[0081] The preparation process of Example 2 is generally the same as that of Example 1. The difference is that 0.018% of Ce is added in Example 2 (-8 < lg[%Si] + 3.8lg[%Ce] = -7.78 < -7). After two VD refinings, the N content of the molten steel is reduced to 0.0108%, and N is 0.0105% and the O content is 0.0015% and the Ce content is 0.0005% after vacuum casting, meeting the target requirements.
[0082] Example 3
[0083] Example 3 is generally the same as Example 1 in the preparation process. The difference is that 0.02% Zr is added before the second LF refining in Example 3. After two VD refinings, the N content is 0.011%. After reheating in the LF furnace and adding 0.015% Zr, the N content is reduced to 0.0089% after the third VD refining, and the N content is 0.0090% and the O content is 0.0011% and the Zr content is 0.0008% after vacuum casting.
[0084] Comparative Example 1
[0085] Comparative Example 1 is generally the same as Example 1 in the preparation process. The difference is that scrap steel and high-carbon ferrochrome with a relatively high N content are used as raw materials in Comparative Example 1, and a martensitic heat-resistant steel ingot is smelted by an electric furnace + LF + VD + protective atmosphere casting process. After the LF refining is completed, the alloy composition is adjusted to the target value, with the Si content being 0.16% and the Al content being 0.011%. After the first VD refining is completed, the N content of the molten steel is 0.016%. After reheating through the LF, the N content of the molten steel is reduced to 0.014% after the second VD refining and further reduced to 0.0135% after the third VD refining. However, the N content of the ingot increases to 0.0150% after protective atmosphere casting, and the O content reaches 0.0032%.
[0086] Comparative Example 2
[0087] Comparative Example 2 is generally the same as Example 1 in the preparation process. The difference is that a martensitic heat-resistant steel is smelted by an electric furnace + LF + VD + vacuum casting process in Comparative Example 2. The refining process of the molten steel is the same as that in Comparative Example 1. After 3 VD refinings, the N content of the molten steel is reduced to 0.0132%, and the N content of the ingot is 0.0128% and the O content is 0.0026% after vacuum casting.
[0088] Comparative Example 3
[0089] Comparative Example 3 is generally the same as Example 1 in the preparation process. The difference is that a martensitic heat-resistant steel is smelted by an electric furnace + LF + VD + protective atmosphere casting process in Comparative Example 3. After the LF refining is completed, the alloy composition is adjusted to the target value, with the Si content being 0.13% and the Al content being 0.0010%. After the first VD refining is completed, the N content of the molten steel is 0.013%. After reheating through the LF, 0.04% metallic Zr is added to the molten steel in the form of zirconium ferroalloy, (-7 < lg[%Si] + 4lg[%Zr] = -6.47). The N content of the molten steel is reduced to 0.011% after the second VD refining, and the N content of the ingot is 0.0108% and the O content is 0.0013% and the Zr content is 0.0012% after vacuum casting. However, the Al content reaches 0.0019%, exceeding the target range.
[0090] Performance testing
[0091] The above Examples 1-3 and Comparative Examples 1-3 were subjected to component detection and inclusion detection, and the detection results are shown in Table 1.
[0092] Table 1 Performance test results
[0093] Group N O D-Class Ds Class Example 1 0.0092% 0.0014% 1.0 0.5 Example 2 0.0105% 0.0015% 1.0 0.5 Example 3 0.0090% 0.0011% 0.5 0.5 Comparative Example 1 0.0150% 0.0032% 1.5 1.0 Comparative Example 2 0.0128% 0.0026% 1.0 0.5 Comparative Example 3 0.0108% 0.0013% 0.5 0.5
[0094] Application Examples
[0095] The ingot obtained in Example 1 was electroslag remelted to ensure that the contents of B, N and Al in the electroslag ingot reached the target values, as shown below:
[0096] Application Example 1
[0097] The method for electroslag remelting of martensitic heat-resistant steel comprises the following steps:
[0098] S1: Electrode preparation: The electrode surface should be fully polished, and there should be no iron oxide scale, shrinkage cavities, or scarring defects on the surface, and oxygenation or the introduction of large-sized foreign inclusions should be avoided;
[0099] The chemical composition of the electrode is shown in Example 1:
[0100] S2: Preparation of pre-melted slag: 50.3% CaF2, 20.1% Al2O3, 23.2% CaO, 2.5% MgO and 2.5% B2O3 are prepared and mixed, melted at a temperature above 1500°C and then water-cooled to obtain pre-melted slag, which is then crushed and baked at about 800°C for 10 hours before use;
[0101] S3: Remelting: Use high-purity argon as the protective atmosphere for electroslag remelting, control the O2 volume fraction in the atmosphere to be no higher than 0.02%, insert the consumable electrode rod into the crystallizer, and start powering on while adding liquid slag; the melting rate v during the remelting process is 0.7×D;
[0102] S4: Feeding: Before the end of remelting, the melting rate is reduced to feed the shrinkage, and the mold is removed after the molten steel is completely solidified to obtain a martensitic heat-resistant steel electroslag ingot;
[0103] The electroslag ingot obtained after remelting was sampled and analyzed, and the B content was 0.0160%, the Al content was 0.0115%, and the N content was 0.0095%.
[0104] Application Example 2
[0105] The preparation process of Application Example 2 is substantially the same as that of Application Example 1, except that the chemical composition mass percentage of the slag system used in Application Example 2 is 54.0% CaF2, 17.8% Al2O3, 21.1% CaO, 3.0% MgO and 1.5% B2O3 and inevitable impurities, and the SiO2 content of the impurities is 0.38%, and the FeO content is 0.28%;
[0106] The electroslag ingot obtained after remelting was sampled and analyzed, and the B content was 0.0120%, the Al content was 0.0101%, and the N content was 0.0095%.
[0107] Comparative application example 1
[0108] The preparation process of Comparative Application Example 1 is substantially the same as that of Application Example 1, except that the chemical composition mass percentage of the slag system used in Comparative Application Example 1 is 51.9% CaF2, 18.6% Al2O3, 21.5% CaO, 2.5% MgO, 4.3% B2O3 and inevitable impurities, and the SiO2 content of the impurities is 0.43%, and the FeO content is 0.37%;
[0109] The electroslag ingot obtained after remelting was sampled and analyzed, and the B content was 0.0250%, the Al content was 0.0104%, and the N content was 0.0098%.
[0110] Comparative Application Example 2
[0111] The preparation process of Comparative Application Example 2 is substantially the same as that of Application Example 1, except that the chemical composition mass percentages of the slag system used in Comparative Application Example 2 are 52.4% CaF2, 19.5% Al2O3, 24.0% CaO, 3.0% MgO and 0.3% B2O3 and inevitable impurities, among which the SiO2 content is 0.39% and the FeO content is 0.26%.
[0112] The electroslag ingot obtained after remelting was sampled and analyzed, and the B content was 0.0038%, the Al content was 0.010%, and the N content was 0.0100%.
[0113] Comparative Application Example 3
[0114] The preparation process of Comparative Application Example 3 is substantially the same as that of Example 1, except that the chemical composition mass percentage of the slag system used in Comparative Application Example 3 is 53.4% CaF2, 19.8% Al2O3, 22.8% CaO and 2.3% B2O3 and inevitable impurities, and the SiO2 content of the impurities is 0.38%, and the FeO content is 0.30%;
[0115] The electroslag ingot obtained after remelting was sampled and analyzed, and the B content was 0.0149%, the Al content was 0.0125%, and the N content was 0.0150%.
[0116] It can be seen from the combination of Application Examples 1-2 and Comparative Application Examples 1-3 that by using the slag system provided by the present invention, the contents of B, N and Al in the obtained electroslag ingots all meet the requirements.
[0117] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for smelting a martensitic heat-resistant steel ingot, characterized in that: The following steps are involved: S1: Add raw materials into an electric furnace for smelting, and tap steel after the temperature rises to 1620-1650°C, and add C to 0.06% for diffusion deoxidation; S2: LF refining stage, active lime and alumina are used to make reducing slag, ferrosilicon alloy is added to make white slag, the temperature is controlled at 1580~1620℃, and it is transferred to the VD station to wait for vacuum degassing; S3: VD first degassing, the first degassing treatment is carried out under high vacuum <133Pa, vacuum carbon deoxidation reaction is used to accelerate denitrification, sampling is carried out after the refining is completed, and the slag is removed to re-make high basicity protection slag; S4: the molten steel after the first degassing by VD is transferred to the LF furnace for re-refining, and the temperature is raised to 1580-1600°C. According to the sampling results, C is added to the lower limit of the composition range of 0.08%, and the composition of other alloy elements except N is adjusted to the target value, and then at least one of Zr, Ce and La is added in the form of ferroalloy for deep deoxidation. After blowing argon for ≥10 minutes, it is transferred to the VD station for secondary degassing; S5: VD second degassing. After VD refining, the N content of the molten steel is tested, C is added to the target composition, and pouring is carried out in a vacuum environment. After cooling and solidification, a martensitic heat-resistant steel ingot is obtained.
2. The method for smelting a martensitic heat-resistant steel ingot according to claim 1, characterized in that: In step S2, the basicity of the reduced slag is not less than 5, and the (FeO) content in the slag is not higher than 0.6%.
3. The smelting method of martensitic heat-resistant steel ingot according to claim 1, characterized in that: In step S3, the components of the high basicity protective slag are CaO, Al2O3, SiO2 and MgO, and the protective slag basicity CaO / SiO2 is not less than 8.
4. The smelting method of martensitic heat-resistant steel ingot according to claim 1, characterized in that: In step S4, the addition amount of Zr, Ce and La satisfies -8 <lg[%Si]+4lg[%Zr]+3.8lg[%Ce]+3.7lg[%La]<-7。 5. The smelting method of martensitic heat-resistant steel ingot according to claim 1, characterized in that: In step S5, if the composition does not meet the target requirement, Zr, Ce, and La deoxidizers are added again and degassing is performed 1 to 2 more times.
6. The method for smelting a martensitic heat-resistant steel ingot according to claim 1, characterized in that: In step S2, the Si content in the molten steel is not less than 0.08%.
7. The method for smelting a martensitic heat-resistant steel ingot according to claim 1, characterized in that: At least one element among Zr, Ce and La is used for deep deoxidation, and the residual content of a single element in the molten steel after VD refining does not exceed 0.003%.
8. A martensitic heat-resistant steel ingot, characterized in that: The martensitic heat-resistant steel ingot is prepared by the smelting method according to any one of claims 1 to 7, and its chemical composition is as follows: C: 0.08-0.14%; Si: ≤0.2%; Al: ≤0.015%; Mn: 0.35-0.80%; Cr: 8.6-9.5%; W: 1.80~2.55%; Mo: 0.20~0.60%; Co: 2.5-3.2%; V: 0.17~0.27%; Nb: 0.04~0.07%; B: 0.010~0.017%; N:0.006~0.012%; O : ≤0.002%, the rest is Fe.
9. A use of a martensitic heat-resistant steel ingot obtained by the smelting method according to any one of claims 1 to 7 or a martensitic heat-resistant steel ingot according to claim 8, characterized in that: The martensitic heat-resistant steel ingot is used as a consumable electrode for electroslag remelting or is directly forged.
10. The use according to claim 9, characterized in that: The martensitic heat-resistant steel ingot is used as a consumable electrode for electroslag remelting. The crystallizer is baked before remelting for a period of not less than 20 minutes. Ar is charged until the O2 content in the furnace is less than 0.2%, and then power is supplied. Remelting is carried out under a protective atmosphere. The remelting slag is a pre-melted slag of CaF2-Al2O3-CaO-B2O3-MgO system.
Citation Information
Patent Citations
Method for smelting martensitic stainless steel P91 for boiler pipe
CN106636953A
Precipitation-hardening martensitic stainless steel 17-4PH smelting technology
CN107385144A
Method of peroxide smelting 16Mn steel by molten steel of electric furnace
CN108467918A
630 DEG C heat-resistant steel and smelting method thereof
CN112899569A
Smelting method for controlling sulfur content of sulfur-containing low alloy steel
CN114134391A